PROBLEMATIC INTERNET USE AND ITS RELATIONSHIP WITH WELL-BEING AND EMOTIONAL INTELLIGENCE ACROSS DIFFERENT GENERATIONS (PRÁXIS EM SAÚDE, 2025)
The study examined problematic internet use, subjective well-being, and emotional intelligence across different generations. A total of 165 individuals participated, divided into three age groups: 18–26, 27–41, and 42–76 years. Participants completed an online survey that included a sociodemographic questionnaire, the Emotional Competence Inventory – Version 3.0 (ECI), the Generalized Problematic Internet Use Scale 2 (GPIUS-2), and the Subjective Well-Being Scale (SWBS). Data were analyzed using descriptive and inferential statistics. Due to non-normality, the Kruskal–Wallis test was applied, and when significant differences were found, the Mann–Whitney test was used. The data indicate that Generation Z showed the highest scores for problematic internet use, along with lower levels of well-being and emotional intelligence. In contrast, Generation X had higher scores for positive emotions and life satisfaction, as well as lower levels of problematic internet use. The results suggest that Generation Z exhibits more problematic internet use and lower levels of well-being and emotional intelligence. Future studies should expand the sample and employ correlational statistics to further explore the relationships among internet use, subjective well-being, and emotional intelligence.
Keywords: Generalized Problematic Internet Use Scale; Subjective Well-Being Scale; Emotional Competence Inventory; Generations; Cross-Cutting Themes